Droxidopa for the Short‐Term Treatment of Symptomatic Neurogenic Orthostatic Hypotension in Parkinson's Disease (nOH306B). Issue 5 (9th December 2014) - Hauser, Robert A.; Isaacson, Stuart; Lisk, Jerome P.; Hewitt, L. Arthur; Rowse, Gerry
ABSTRACT Neurogenic orthostatic hypotension (nOH) results from failure of norepinephrine responses to postural change to maintain standing systolic blood pressure (s‐SBP). Droxidopa is an oral prodrug of norepinephrine. Study nOH306 enrolled patients with Parkinson's disease (PD) and symptomatic nOH. Subjects underwent up to 2 weeks of double‐blind titration of droxidopa or placebo, followed by 8 weeks of double‐blind maintenance treatment (100‐600 mg thrice‐daily). For the initial 51 subjects (study nOH306A, previously reported), the primary efficacy measure, Orthostatic Hypotension Questionnaire (OHQ) composite score, did not demonstrate significant change versus placebo at maintenance week 8. For the subsequent 171 subjects (study nOH306B, reported here), the primary efficacy measure was change versus placebo on item 1 ("dizziness, lightheadedness, feeling faint, or feeling like you might black out") of the Orthostatic Hypotension Symptom Assessment (OHSA) subsection of the OHQ at maintenance week 1. At week 1, mean (standard deviation) improvement on OHSA item 1 was 2.3 (2.95) for droxidopa versus 1.3 (3.16) for placebo (P = 0.018). In addition, mean increase in s‐SBP at week 1 was 6.4 (18.85) for droxidopa versus 0.7 (20.18) mmHg for placebo (nominal P value: 0.032). Differences in change in OHSA item 1 scores from baseline to maintenance weeks 2, 4, and 8 were not statistically significant. Adverse‐event (AE) incidence was similar across groups, but 12.4% of droxidopa and 6.1% of placebo subjects withdrew because of AEs. The most common AEs on droxidopa (vs. placebo) were headache (13.5% vs. 7.3%) and dizziness (10.1% vs. 4.9%). Study nOH306B demonstrated subjective (OHSA item 1) and objective (s‐SBP) evidence of short‐term droxidopa efficacy (vs. placebo) for symptomatic nOH in PD. © 2014 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.